Analysis of the University Institution Through the Leadership Exercised by University Students: An Approximate Study at the University of Granada. - HOMRANI, Mohammed (2017)
In this article, we present a descriptive research, carried out at the University of Granada. With the objective of analyzing university students' self-perception about their role as university leaders, a mixed methodological design was developed in which a questionnaire was passed, semi-structured interviews were conducted and discussion groups were given to a total sample of 80 students University professors who held positions of representation and actively participated in the various governing bodies of the University. This research is justified on the need to encourage the participation of the majority population, the student, in the curricular, organizational and political decisions of the university. At the same time, the fact that students are the main affected in these, further support the realization of this study. The results show a gradual increase in the level of involvement of university students to access the University management and participation bodies. However, at the same time and, we want to highlight the lack of diffusion and promotion of this figure of leadership, by the different positions of university government.